Impact of computed tomography parameters on radiation dose in chest imaging: a comparative study between tomographs - Warley Ferreira Felix; Adriana de Souza Medeiros Batista; Arno Heeren de Oliveira; Marcos Eugênio Silva Abrantes (Brazilian Journal of Radiation Sciences, 2025)
Due to the declaration of the Covid-19 pandemic by the World Health Organization in 2020, there was a significant increase in imaging exams to evaluate lung problems, these being the organs most affected by the disease. Given this demand, it is essential to understand how changes in the basic parameters of tomography exam protocols influence the doses of ionizing radiation received by patients. For this study, two test objects were used, one filled with water and the other with water containing areas of different densities. The study was carried out with a scan length of 70 mm each, to check variations in Hounsfield Units (HU) between exam protocols through statistical analyzes using the SPSS 21 software. For this purpose, scans were carried out on chest protocols routine on two computed tomography scanners from the same manufacturer, one with 4 rows and the other with 64, but with different tomographic image acquisition parameters. The scanning parameters used in the 64 rows tomograph were voltage of 120 kVp, modulated electric current, X-ray tube rotation time of 0.5 second, slice thickness of 2.0 mm, intervals between slices of 1.0 mm and spiral pitch of 0.828 and in the tomograph 4 rows, voltage 120 kVp, modulated electric current, X-ray tube rotation time of 0.75 seconds, slice thickness of 4.0 mm, interval between slices of 2.0 mm, spiral pitch of 1.0. The comparative results of the doses in the CT scanners showed that, in the 4 rows CT scanner, the total milliampere seconds (mAs) was 15.43% and the scanning time was 52.33% longer compared to the 64 rows CT scanner. However, the volume-weighted computed tomography dose index value (CTDIVOL), the dose-length product (DLP) and the effective dose (E) were, respectively, 34.74%, 49.46% and 50.46% lower in the 4 rows tomography scanner compared to the 64 rows tomography scanner, which leads us to identify which parameters of the tomographic examination contribute to this 50% reduction in the effective dose between the tomography scanners. The identification of these parameters in protocols will reference the development of protocols with low doses of ionizing radiation, which will allow the optimization of exposure of patients who require evolutionary monitoring of pathologies through tomographic images.